Research on meta universe NFT artwork design method based on artificial intelligence for enterprise development strategy - Menon, Dr.Satish (The journal of contemporary issues in business and government, 2022)
At this stage, the foundation of the meta universe technology has been preliminary completed, in which the artificial intelligence technology carries the communication between the subject and object of the meta universe, and the most important technical support for its economic system to build a credible cooperation mechanism is the blockchain technology, which includes non homogeneous digital assets (NFT), This research constructs an analysis of the design of meta universe NFT artworks based on artificial intelligence design methods under the background of enterprise development strategy. Through the analysis and comparison of data on the generation logic, technical attributes, technical and legal risk assessment and legal protection status of meta universe NFT artworks under different design methods, the research results show that, The meta universe NFT artworks under the artificial intelligence design method are more suitable for the current audience’s preferences and can meet their needs.Artificial intelligence meta universe NFT art design,the development of digital industry has entered a new stage,it can change the traditional virtual commodity trading mode, so that users can trade freely, greatly enhancing the efficiency of data asset trading.